2019
DOI: 10.1101/723387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polarized Lung Inflammation and Tie2/Angiopoietin-Mediated Endothelial Dysfunction during SevereOrientia tsutsugamushiInfection

Abstract: 27 of Texas Medical Branch, 301 University Blvd, Galveston, TX 77555-0435 28 #d Current Address: Department of Physiology, OUHSC, 940 Stanton Young Blvd., Oklahoma 29 City, OK 73104-5042 30 31 32 33 * Corresponding Authors: Jinjun Liu: jupet@163.com; Lynn Soong: lysoong@utmb.edu 34 35 36 Abstract 38Orientia tsutsugamushi infection can cause acute lung injury and high mortality in humans; 39 however, the underlying mechanisms are unclear. Here, we tested a hypothesis that dysregulated 40 pulmonary inflammati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Dysregulated inflammation is particularly deleterious and often associated with endothelial cell dysfunction. Trent et al [ 31 ] reported dysregulated pulmonary inflammation and Tie-2-related endothelial dysfunction contributing to lung damage and mortality in a murine model of Orienta Tsutsugamushi infection. Tissue findings included a high level of Ang-2 proteins in pulmonary endothelial cells, a progressive loss of endothelial cell quiescent and junction proteins, and a substantial decrease in Tie-2 receptor at the transcriptional and functional levels.…”
Section: How Do Endothelial Cells Facilitate Repair?mentioning
confidence: 99%
“…Dysregulated inflammation is particularly deleterious and often associated with endothelial cell dysfunction. Trent et al [ 31 ] reported dysregulated pulmonary inflammation and Tie-2-related endothelial dysfunction contributing to lung damage and mortality in a murine model of Orienta Tsutsugamushi infection. Tissue findings included a high level of Ang-2 proteins in pulmonary endothelial cells, a progressive loss of endothelial cell quiescent and junction proteins, and a substantial decrease in Tie-2 receptor at the transcriptional and functional levels.…”
Section: How Do Endothelial Cells Facilitate Repair?mentioning
confidence: 99%
“…Bacteria were added at a multiplicity of infection (MOI) of 5 or 10 and centrifuged at 2,000 RPM for 5 min to synchronize infection. The Karp strain of O. tsutsugamushi was utilized for all infections using the same bacterial stocks prepared from Vero cells, as described previously [24,27]. Experiments were performed in triplicate or quadruplicate.…”
Section: Infection Of Mouse Bone Marrow-derived Macrophages (Mφ)mentioning
confidence: 99%
“…Monocytes and Ms are significant sources of type 1 cytokines, including IL-12 and TNF, during infectious processes [29,30]. Considering that animal models of scrub typhus display robust M recruitment and type 1 responses in multiple organs [14,25,27], we evaluated whether Sykdependent signaling may play a role in generating such responses in vitro. After infection with O. tsutsugamushi (5 MOI), we observed statistically significant increases in M Il12p40, Tnf, and Il27p28 transcript levels at 4 hpi, with peak expression for all cytokines occurring at 6 hpi (Figure 3).…”
Section: Type 1 Cytokine Production Is Reliant On Syk Signaling In Mmentioning
confidence: 99%
“…O. tsutsugamushi has long been known to be a potent inducer of monocyte-related chemokines in humans and mice ( 2 4 ). Robust evidence supports a macrophage/monocyte tropism for this pathogen in blood and tissue ( 1 , 5 , 6 ) and strong macrophage responses in infected tissues ( 7 , 8 ). Moreover, O. tsutsugamushi infects and replicates in human blood-derived monocytes ex vivo , as it does in neutrophils ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, in the lung of human patients, the typical finding is an interstitial pneumonia, which seems to be associated with disease severity ( 34 36 ). While it was shown that Orientia drives M1 responses in the lungs ( 8 ), no mechanistic studies on chemokine-driven recruitment of myeloid cells have been provided yet. In the present study, we hypothesized that CCR2 is critical for the development of pulmonary monocyte/macrophage responses and associated bacterial clearance in Orientia infection.…”
Section: Introductionmentioning
confidence: 99%